Gestational Choriocarcinoma Manifesting as Spontaneous Hemothorax in Third Trimester of Pregnancy: A Case Report - Devaraj, Suma; Panda, Soumya Surath; Sahu, Debasish; Mohapatra, Debahuti; Agarwal, Beena Devi; Biswas, Ghanashyam; Moharana, Lalatendu; Kilaru, Sindhu; Kolluri, Spoorthy (Indian Journal of Medical and Paediatric Oncology, 2022)
Gestational trophoblastic neoplasia (GTN) is an aggressive malignancy arising from the trophoblastic tissue. It is rarely seen in association with advanced intrauterine pregnancy. Most common manifestations are due to bleeding caused by the rich vascularity of trophoblastic tissue. We describe here a case of a 28-year-old female patient who presented to us at 32 weeks of pregnancy with sudden onset dyspnea and hemodynamic instability. On evaluation, imaging techniques revealed a gross left hemothorax requiring intercostal tube insertion for stabilization. Emergency thoracotomy and hemothorax drainage were performed wherein a tumor mass in the lower lobe of left lung was identified and resected. Histopathological examination confirmed the diagnosis of choriocarcinoma. Beta HCG levels were found to be elevated. Final diagnosis of a FIGO stage IV high-risk gestational choriocarcinoma was made. Following this, six cycles of multi-agent EMA-CO chemotherapy was administered to the patient. Patient had an excellent response to treatment with documented serial fall in β HCG levels and she continues to be in remission after 6 months of follow-up. In conclusion, in the circumstance of any pregnant women presenting with abnormal bleeding symptoms such as hemothorax, choriocarcinoma as a cause should be considered for early diagnosis and effective management.
Keywords: gestational choriocarcinoma; hemothorax; pregnancy